Culturally Responsive Teaching In Thai Classroom Settings: A Perspective From Indonesian Educators - Reskyani Reskyani; Andi Adisaturrahimi; Mustaqimah Mustaqimah; M. Jufrianto; Sami’an Wulandari; Nur Ainun Musa; Amaliah Ramdani (JELITA, 2024)
A culturally responsive teaching approach is best applied in classes where students have different cultural backgrounds. This research aims to find out how culturally responsive teaching in Thai classroom settings: a perspective from Indonesian educators. Therefore, this research methodology used a qualitative research strategy with the interview method as the main data collection technique. This research used semi-structured interviews, accepting three Indonesian teachers who had experience teaching in Thailand. This research also aims to determine the implementation and dynamics of culturally sensitive practices in Thai classrooms with special reference to the process of cultural assimilation in learning institutions. So from the results of this research, the researchers found 5 categories, namely: a. Teaching Experience in Thailand and its distinct difference from other countries. b. Integration of Thai Cultural Aspects in Teaching. c. Challenges in Implementing Culturally Responsive Approach. d. Student Response to Culturally Responsive Teaching Approach. e. Suggestions or Recommendations for Other Teachers. The findings of this research are useful for educational practitioners and stakeholders as well as researchers who have a desire to teach thoughtfully in the context of Thai culture or other similar cultural environments.